GERAKAN PENGENTASAN PENGANGGURAN TERDIDIK MELALUI STRATEGI PERGURUAN TINGGI DALAM MENINGKATKAN KEWIRAUSAHAAN BAGI MAHASISWA DI PENDIDIKAN TINGGI - Iskandar Iskandar; Fery Sudarwadi (Universitas Sebelas Maret, 2020)
The purpose of this study are to find out what strategies were used at universities in increasing entrepreneurship for students, including to find out the general vision of entrepreneurship for students. this type of research was qualitative descriptive research, the procedure for collecting data is obtained using interview methods, and supported by documentation and observation, then the data is analyzed to obtain conclusions and verification. The results of the study explained that there were several strategies used by STKIP PGRI Sumenep in entrepreneurship for students including: prioritizing entrepreneurship, compiling curriculum and increasing lecturer HR, increasing labor competency and productivity for students, establishing campus entrepreneurship centers, forming student business units , KKN-business, entrepreneurship internship, and student creative programs, the development of entrepreneurial student programs, forming entrepreneurship centers, cooperation with the business world and financial institutions, entrepreneurship awards, the policy of having a business as a condition for student graduation.Key words: College Strategy, Educated Unemployment, Entrepreneurship